2017
DOI: 10.1002/jnr.24117
|View full text |Cite
|
Sign up to set email alerts
|

A new model for netrin1 in commissural axon guidance

Abstract: Now-classic experiments characterized netrin1 as a major player in commissural axon guidance in the spinal cord. The data suggest a chemotactic model in which netrin1 expression in the floor plate forms a concentration gradient that attracts commissural axons. New research published independently in Neuron and in Nature tests this model by deleting netrin1 specifically in the floor plate. Surprisingly, these conditional mutant mice have no overt commissure defects. The authors report that netrin1 decorates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…One current model suggests that the pial-netrin-1 substrate acts by haptotaxis to promote commissural axon extension and direct axons toward the ventral midline. Other excellent papers detailed the functions of netrin-1 in guiding the commissural axons to the ventral midline ( Morales, 2018 ; Chedotal, 2019 ; Comer et al, 2019 ; Ducuing et al, 2019 ). Importantly, draxin is also heavily deposited in the basement membrane along the dorsal and lateral sides of the spinal cord ( Figure 2A ; Islam et al, 2009 ), suggesting a role of pial-draxin in commissural axon guidance.…”
Section: Spinal Commissural Axonsmentioning
confidence: 99%
“…One current model suggests that the pial-netrin-1 substrate acts by haptotaxis to promote commissural axon extension and direct axons toward the ventral midline. Other excellent papers detailed the functions of netrin-1 in guiding the commissural axons to the ventral midline ( Morales, 2018 ; Chedotal, 2019 ; Comer et al, 2019 ; Ducuing et al, 2019 ). Importantly, draxin is also heavily deposited in the basement membrane along the dorsal and lateral sides of the spinal cord ( Figure 2A ; Islam et al, 2009 ), suggesting a role of pial-draxin in commissural axon guidance.…”
Section: Spinal Commissural Axonsmentioning
confidence: 99%
“…The original studies on the function of netrin-1 in vivo relied on a hypomorphic gene trap allele of Ntn1 that maintained low levels of netrin-1 protein ( Serafini et al, 1996 ), however, recent development of mice carrying a floxed Ntn1 allele has allowed for tissue-specific and complete loss of netrin-1 ( Bin et al, 2015 ; Yung et al, 2015 ). Three recent papers have galvanized the potential role of netrin-1 as a haptotactic cue in vivo by selectively deleting netrin-1 from the floor plate and/or ventricular zone of the spine and hindbrain using floxed Ntn1 alleles, and assessing the midline crossing of commissural axons ( Dominici et al, 2017 ; Varadarajan et al, 2017 ; Yamauchi et al, 2017 ) (for an additional mini-review on Dominici et al and Varadarajan et al, see Morales, 2018 ). All three groups found that netrin-1 expression in the floor plate, originally thought to be the source of the attractive gradient of netrin-1 responsible for commissural crossing ( Maclennan et al, 1997 ; Kennedy et al, 2006 ), is not necessary for commissure formation.…”
Section: Netrin-1 the Classical Guidance Cuementioning
confidence: 99%
“…Classically, Netrin was thought to establish a ventral-to-dorsal gradient, which was followed by growth cones growing up the gradient (attraction) or down the gradient (repulsion) (SERAFINI et al 1996;FAZELI et al 1997;KENNEDY et al 2006). Recent studies in vertebrate spinal cord and our studies in C. elegans suggest a distinct mechanism (DOMINICI et al 2017;VARADARAJAN et al 2017;YAMAUCHI et al 2017;MORALES 2018). In the spinal cord, floorplate Netrin1 was found to be dispensable for ventral commissural axon guidance.…”
Section: Introductionmentioning
confidence: 55%